Incidence Rate and Etiological Factors of Pancreatitis in Alcoholic and Non-alcoholic Patients - Buyyakari Shirisa; Paramasivam Suresh Kumar; Rakesh Das (Current Research in Pharmaceutical Sciences, 2017)
To study the incidence and etiological factors of pancreatitis in both alcoholics and non alcoholic patients.serum amylase and lipase levels were compared in alcoholics and non alcoholics. This is a prospective observational study conducted in district head Quarter hospital, Khammam. Total 100 in-patients are included in this study according to inclusion and exclusion criteria. Detailed history of patients were considered along with physical and laboratory examination, ultra sound examination for the conformation of etiological factor of pancreatitis in patients has been made. In our study, out of all, 116 patients have conformed that alcohol is the main etiological factor and remaining 26 of patients were from nonalcoholic history. The patients with alcoholic etiology were 93 patients. Out of 142 patients, 96 patients have acute pancreatitis and remaining 26 patients have chronic pancreatitis. The patients with nonalcoholicetiology were 26 patients. Out of 26 patients, 20 patients have gall stones, 2 patients have hypercalcemia and 2 patients have triglyceredemia. The study concludes that alcohol is the major cause of pancreatitis in patients. Serum amylase and lipase levels are high in alcoholics than the non- alcoholic and the gall stone is the main cause in non-alcoholic patients for pancreatitis.